Solar power from North Africa: Frameworks and prospects - Isabelle Werenfels; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2010)
The idea of generating solar electricity in the Sahara Desert and exporting it to Europe is captivating, both from the climate and energy perspective and with an eye to Europe's goal of intensifying cooperation with its southern neighbours. Correspondingly great has been the political and media interest provoked by the Mediterranean Solar Plan launched in 2008 by the Union for the Mediterranean and the private-sector Desertec Industrial Initiative, founded in 2009 by a consortium led by Münchener Rück. But if these highly ambitious projects are to become reality, a proper financial, political, legal and regulatory framework will need to be put in place.The obstacles are legion: At the level of nation-states, nationalism and structural conservatism continue to impede energy policy. The will to create the green electricity market required for commercial viability is lacking at the EU level, while in the southern Mediterranean the investment conditions are problematic. But there are few alternatives and the time is ripe: in Europe where power stations and transmission grids are due for modernisation, and in North Africa where rapidly growing electricity consumption is forcing states to look around for new sources of energy. But the fundamental decisions need to be taken now - even if the electricity is not to flow until 2050. It would make sense to start straight away with high-visibility landmark projects, setting aside the idea of physical export of electricity for the moment and introducing virtual trading instead. Politically, the need is to promote a stable legal framework at all levels
Keywords: 320